American Literature and Culture in an Age of Cold War : A Critical Reassessment - Belletto, Steven; Grausam, Daniel, 1975- (Book collections on Project MUSE., 2012)
This text aims at reassessing Cold War culture - both because its full cultural impact remains unprocessed and because some of the chief paradigms for understanding that culture may confuse rather than clarify. A collection of the work of cultural critics writing about the period, this book reveals a broad range of ways that American cultural production from the late 1940s to the present might be understood in relation to the Cold War.